Comparison of first-line chemotherapy based on irinotecan or other drugs to treat non-small cell lung cancer in stage IIIB/IV: a systematic review and meta-analysis. Issue 1 (December 2015) - Yang, Xue-Qin; Li, Chong-Yi; Xu, Ming-Fang; Zhao, Hong; Wang, Dong
Abstract Background To compare the efficacy and toxicity of irinotecan-based chemotherapy (IBC) and non-irinotecan-based chemotherapy (NIBC) as first-line treatment for stage IIIB/IV non-small cell lung cancer (NSCLC). Methods PubMed, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), abstracts from the annual meetings of ASCO and the ESMO up to 2014 were searched for randomized controlled trials (RCTs) that compared IBC with NIBC. Data on overall survival (OS) and progression-free survival (PFS) were meta-analyzed to provide hazard ratios (HRs), while data on overall response rate (ORR) and frequencies of toxicity were meta-analyzed to provide relative risk ratios (RR). Results Seven RCTs (6 RCTs from Asian population and 1 from non-Asian population) involving 1473 patients with previously untreated stage IIIB/IV NSCLC were included in the meta-analysis. IBC and NIBC were associated with similar ORR (RR: 1.08, 95 %CI: 0.94 to 1.23, p  = 0.30), OS (HR: 0.97, 95 %CI: 0.88 to 1.07, p  = 0.56), and PFS (HR: 1.02, 95 %CI: 0.97 to 1.08, p  = 0.38). However, the subgroups between Asian and non-Asian patients differed significantly in OS (HR: 0.94 vs 1.87, p  = 0.007). There was no significant difference for hematological toxicity (RR: 0.79, 95 %CI: 0.60 to 1.04, p  = 0.09) and significant worse for non-hematological toxicity (RR: 2.28, 95 %CI: 1.60 to3.24, p  < 0.001), when IBC compared to NIBC. Conclusions As the available evidence suggests that IBC and NIBC are equivalent in terms of ORR, PFS, OS, at least in Asian patients, we recommend that IBC be considered as a first-line treatment in Asian patients with stage IIIB/IV NSCLC. However, the non-hematological toxicity of IBC must be considered.